IL-1 and TNF mediates IL-6 signaling at the maternal-fetal interface during intrauterine inflammation - Presicce, Pietro; Roland, Cynthia; Senthamaraikannan, Paranthaman; Cappelletti, Monica; Hammons, McKensie; Miller, Lisa A.; Jobe, Alan H.; Chougnet, Claire A.; DeFranco, Emily; Kallapur, Suhas G. (Frontiers in Immunology, 2024)
IL6 signaling plays an important role in triggering labor and IL6 is an established biomarker of intrauterine infection/inflammation (IUI) driven preterm labor (PTL). The biology of IL6 during IUI at the maternal-fetal interface was investigated in samples from human subjects and non-human primates (NHP). Pregnant women with histologic chorioamnionitis diagnosed by placenta histology were recruited (n=28 term, n=43 for preterm pregnancies from 26-36 completed weeks of gestation). IUI was induced in Rhesus macaque by intraamniotic injection of lipopolysachharide (LPS, n=23). IL1 signaling was blocked using Anakinra (human IL-1 receptor antagonist, n=13), and Tumor necrosis factor (TNF) signaling was blocked by anti TNF-antibody (Adalimumab n=14).The blockers were given before LPS. All animals including controls (intraamniotic injection of saline n=27), were delivered 16h after LPS/saline exposure at about 80% gestation. IUI induced a robust expression of IL6 mRNAs in the fetal membranes (chorion-amniondecidua tissue) both in humans (term and preterm) and NHP. The major sources of IL6 mRNA expression were the amnion mesenchymal cells (AMC) and decidua stroma cells.Additionally, during IUI in the NHP, ADAM17 (a protease that cleaves membrane bound IL6 receptor (IL6R) to release a soluble form) and IL6R mRNA increased in the fetal membranes, and the ratio of IL6 and soluble forms of IL6R, gp130 increased in the amniotic fluid signifiying upregulation of IL6 trans-signaling. Both IL1 and TNF blockade suppressed LPS-induced IL6 mRNAs in the AMC and variably decreased elements of IL6 trans-signaling. These data suggest that IL1 and TNF blockers may be useful antiinflammatory agents via suppression of IL6 signaling at the maternal-fetal interface.